2009
DOI: 10.1080/10810730903032986
|View full text |Cite
|
Sign up to set email alerts
|

Presentation Format Affects Comprehension and Risk Assessment: The Case of Prenatal Screening

Abstract: We studied the effects of presentation formats (frequency, 1-in-N, and visual) and numeracy level on students' understanding of prenatal screening results, as well as their risk assessment for having a fetus with Down syndrome. Frequency format (vs. 1-in-N and visual formats) improved participants' ability to accurately assess the chances of having a fetus with Down syndrome, and was associated with lower risk estimates. High numeracy levels were associated with a better ability to judge risk likelihood. For i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…For example, in a study conveying risk reduction of medications for Crohn’s disease, the visual Cates Plot was less convincing and less preferred by participants[26]. Another small study of prenatal screening data found that patients with low numeracy actually did better with a frequency rather than visual schema[27]. This may be due to the fact that numeracy and graphicacy are correlated[28], so the design of the graph or picture is just as crucial to understanding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study conveying risk reduction of medications for Crohn’s disease, the visual Cates Plot was less convincing and less preferred by participants[26]. Another small study of prenatal screening data found that patients with low numeracy actually did better with a frequency rather than visual schema[27]. This may be due to the fact that numeracy and graphicacy are correlated[28], so the design of the graph or picture is just as crucial to understanding.…”
Section: Discussionmentioning
confidence: 99%
“…All numerical formats are not equivalent, however, and considerable research has compared, for example, the pros and cons of using frequency formats instead of percentages [1-4] and the potential pitfalls of specific formats such as 1-in-X [5,6] and number needed to treat [7]. In addition, research on affective influences on risk perceptions make it clear that the same risk number can lead to very different feelings about that risk based on different circumstances, presentations, or contexts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patient decision aids and other patient communications that incorporate risk statistics will only be effective in improving patient decision making if they use design features that make these risk communications easier to understand. In this vein, researchers have evaluated the benefits of giving people more intuitive representations of risks by, for example, using frequencies instead of percentages [5-8] and testing a wide variety of visual displays, such as bar graphs, pie charts, and pictographs or icon arrays [9-14]. …”
Section: Introductionmentioning
confidence: 99%